2023
DOI: 10.3389/fendo.2023.1151199
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between clinical-psychological features and bone mineral density changes in post-menopausal women undergoing anti-osteoporotic treatment: a two-year follow-up

Abstract: IntroductionPsychological features have been bidirectionally associated with osteoporosis, but it is still unclear whether patient’s anxiety fluctuations during the anti-osteoporotic treatment can have an impact on bone mineral density (BMD) variation. The aim of this study was to investigate the interrelations between psychological distress features, such as anxiety, depression, health-related QoL (HRQoL) and bone health in women receiving anti-osteoporotic treatment.Methods192 post-menopausal osteoporotic wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Studies have shown that living alone or transitioning from living with others significantly increases the risk of osteoporosis compared to non-living alone older adults [ 6 , 7 ]. This may be due to a lack of socialization and social support, malnutrition, and poor psychological well-being [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that living alone or transitioning from living with others significantly increases the risk of osteoporosis compared to non-living alone older adults [ 6 , 7 ]. This may be due to a lack of socialization and social support, malnutrition, and poor psychological well-being [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%